دور الرقابة والإشراف على قطاع التأمین في الجزائر - بديس, سواعدي (جامعة المسيلة, 2021)
This study dealt with the extent of the importance and inevitability of control and supervision over the insurance sector, especially in light of liberalization and openness. in Algeria. The most important thing we have concluded by addressing the subject is that in light of the liberalization and openness of the market and the entry of many foreign companies competing in the field of insurance, the state must update and develop policies and mechanisms of supervision and control and make them strict and clear, by studying the problems that impede the insurance market and formulating appropriate emergency solutions and plans And in line with the systems in force in various